2022
DOI: 10.1186/s12877-022-03009-3
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and coping strategies of older adults in Hong Kong during COVID-19 pandemic: a mixed methods study

Abstract: Background Despite the adverse physical health impact of COVID-19 on older adults, whether they are psychosocially vulnerable under the pandemic remains debatable. In this mixed methods study, we examined the psychosocial vulnerability of older adults relative to their younger counterparts and explored how they coped with the pandemic. Methods From September to October 2020, 1067 adults in Hong Kong were randomly sampled and completed a telephone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
5
30
1
3
Order By: Relevance
“…It seems that given their age, at that moment, they did not think much about their death or life. The results presented in this manuscript confirm the findings of Chan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…It seems that given their age, at that moment, they did not think much about their death or life. The results presented in this manuscript confirm the findings of Chan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although women life expectancy is higher than men, women are overrepresented in this study and a wider range of men sample is needed. In addition, the are some variables not explored in this study, like religion [ 56 ], chronic medical illness [ 57 ] and economic security [ 58 ]. Moreover, we did not include established QoL indicators, and the internal consistency of personal growth is weak and for this reason the results could be not generalized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, internet cognitive behavior therapy was tested, and it was useful and cost-effective [ 61 ], and also helped to treat insomnia [ 62 ] and even avoid the spread of the infection during the pandemic situation [ 63 ]. Moreover, the use of life-story review can reduce depression in older adults and can help them to review their life, providing an emotional catharsis and strengthen resilience [ 58 ]. However, the digital divide in older people should be solved to assure the accessibility to online interventions [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the time lag of our study, the observed apparent social gradients of mental illnesses could be further exacerbated by social unrest and the ongoing COVID-19 pandemic [ 44 ], which is alarming and warrants policy actions. Recent studies found that the COVID-19 pandemic had serious impacts on individual mental health and socioeconomic inequality as mental health still exists during the pandemic, both internationally [ 45 , 46 ] and in Hong Kong [ 47 , 48 , 49 , 50 , 51 ]. Specifically, deprived individuals had worse mental health scores via concerns over livelihood and economic activity (e.g., unemployment or job instability), which were likely to be exacerbated by the stringent COVID-19 containment measures in Hong Kong [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%